Cardiotoxicity in pediatric lymphoma survivors. (2nd November 2021) - Bansal, Neha; Joshi, Chaitya; Adams, Michael Jacob; Hutchins, Kelley; Ray, Andrew; Lipshultz, Steven E.
ABSTRACT: Introduction: Over the past five decades, the diagnosis and management of children with various malignancies have improved tremendously. As a result, an increasing number of children are long-term cancer survivors. With improved survival, however, has come an increased risk of treatment-related cardiovascular complications that can appear decades later. Areas Covered: This review discusses the pathophysiology, epidemiology and effects of treatment-related cardiovascular complications from anthracyclines and radiotherapy in pediatric lymphoma survivors. There is a paucity of evidence-based recommendations for screening for and treatment of cancer therapy-induced cardiovascular complications. We discuss current preventive measures and strategies for their treatment. Expert Opinion: Significant cardiac adverse effects occur due to radiation and chemotherapy received by patients treated for lymphoma. Higher lifetime cumulative doses, female sex, longer follow-up, younger age, and preexisting cardiovascular disease are associated with a higher incidence of cardiotoxicity. With deeper understanding of the mechanisms of these adverse cardiac effects and identification of driver mutations causing these effects, personalized cancer therapy to limit cardiotoxic effects while ensuring an adequate anti-neoplastic effect would be ideal. In the meantime, expanding the use of cardioprotective agents with the best evidence such as dexrazoxane should be encouraged and further studied.